2018
DOI: 10.1038/s41396-018-0098-9
|View full text |Cite
|
Sign up to set email alerts
|

Genomic expansion of magnetotactic bacteria reveals an early common origin of magnetotaxis with lineage-specific evolution

Abstract: The origin and evolution of magnetoreception, which in diverse prokaryotes and protozoa is known as magnetotaxis and enables these microorganisms to detect Earth’s magnetic field for orientation and navigation, is not well understood in evolutionary biology. The only known prokaryotes capable of sensing the geomagnetic field are magnetotactic bacteria (MTB), motile microorganisms that biomineralize intracellular, membrane-bounded magnetic single-domain crystals of either magnetite (Fe3O4) or greigite (Fe3S4) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
161
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(164 citation statements)
references
References 62 publications
3
161
0
Order By: Relevance
“…Results presented here strongly indicate an early origin of magnetoreception in the domain Eukarya , a development probably evolving from a protistan ancestor that was able to synthesize magnetic nanoparticles similar to those of MTB from deeply branching phylogenetic groups. Currently, the evolution of magnetotaxis and magnetosome biomineralization in MTB is explained based on vertical and horizontal gene transfer, as well as by gene loss and gene duplication events (Lin et al ., ). Studies of magnetotactic protists would likely provide significant additional information in the evolution of magnetoreception in organisms that respond in some way to the Earth's magnetic field.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Results presented here strongly indicate an early origin of magnetoreception in the domain Eukarya , a development probably evolving from a protistan ancestor that was able to synthesize magnetic nanoparticles similar to those of MTB from deeply branching phylogenetic groups. Currently, the evolution of magnetotaxis and magnetosome biomineralization in MTB is explained based on vertical and horizontal gene transfer, as well as by gene loss and gene duplication events (Lin et al ., ). Studies of magnetotactic protists would likely provide significant additional information in the evolution of magnetoreception in organisms that respond in some way to the Earth's magnetic field.…”
Section: Discussionmentioning
confidence: 97%
“…Representatives of this group are present in a number of phyla including several classes of the Proteobacteria (Sakaguchi et al ., ; Lefèvre et al ., ; Morillo et al ., ; Taoka et al ., ; Abreu et al ., ), the Nitrospirae (Lefèvre et al ., ; Lin et al ., ) and the candidate phylum Omnitrophica (Kolinko et al ., , ). Culture‐independent methods and single‐cell genome analysis indicate that the diversity and phylogenetic distribution of magnetotactic organisms are underestimated (Kolinko et al ., ; Rinke et al ., ) and may extend to other phylogenetic groups including the phyla Latescibacteria and Planctomycetes (Lin and Pan, ; Lin et al ., ; Lin et al ., ) or maybe even other domains of life (Torres de Araujo et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Biomineralization of magnetic iron oxide and iron sulfide crystals by bacteria is a fascinating function whose underlying genetic determinism, molecular machinery, ecologic role and evolution have been the focus of an increasing number of investigations lately (Lefèvre et al, 2011;Lefèvre and Bazylinski, 2013;Hershey et al, 2016;Toro-Nahuelpan et al, 2016;Uebe and Schüler, 2016;Lin et al, 2017bLin et al, , 2018. To date, this ability has been observed in Gram-negative magnetotactic bacteria (MTB) only, which are commonly found at the oxic-anoxic interface (OAI) of any stratified freshwater or marine environment with an O 2 /redox gradient (Bazylinski and Frankel, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous biodiversity studies revealed the intriguing polyphyletism of magnetic biomineralization within the bacteria domain (Lin et al, 2018). Most of the MTB described so far belong to three classes of Proteobacteria, and some are affiliated to the Nitrospirae and Omnitrophica phyla Lin et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…MTB present various morphotypes including cocci, spirilla, rod-shaped, vibrio, and more complex multicellular aggregates and have been found in aquatic environments from freshwater to marine ecosystems (Blakemore, 1975;Bazylinski and Frankel, 2004;Lefevre and Bazylinski, 2013). Phylogenetically, magnetotactic bacteria are members of several classes of the Proteobacteria phylum including the Alpha-, Gamma-, Delta-, Zeta-, candidate Lambda-, candidate Eta-classes, the Nitrospirae phylum, the candidate Omnitrophica phylum, the candidate Latescibacteria phylum and the Planctomycetes phylum (Lin et al, 2017a;Lin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%